The Mediating Effect of Operational Capabilities: How the Construction Materials Industry in Indonesia Improves Its Operational Performance through Supply Chain Management - Jeremiah, Aldrich; Ongkowijoyo, Gracia (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of Collaborative Supply Chain Management (CSCM) and Supply Chain Adaptability (SCA) on the Operational Performance (OP) of the building materials industry in Indonesia. The research utilized online survey data to analyze 93 companies. The analysis of the data was conducted through PLS-SEM using the SmartPLS3 software. The results show that CSCM shows a positive but negligible impact on OP, while SCA does not have an effect on OP. However, the effect of CSCM and SCA on operational performance is significant and positive through a full mediation by operational capabilities. The conclusion emphasizes that external strategy success depends on strengthening internal resources, highlighting the importance of operational capability development as a core element for performance improvement.